Abelard's love [Abaelards Liebe] - Rinser, Luise 1911-2002 (European women writers series., 1998)
The doomed romance of Abelard, a 12th century French teacher of philosophy and his pupil, Heloise, which led to his castration and her confinement in a convent. The relationship is recounted in the form of letters, written to Heloise by their son, Astrolabe.